PENGARUH PENERAPAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PERUSAHAAN (Studi pada PT Angkasa Pura II) - Rahmatika, Nurmaria; Agus, Restu (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
The objective of this study is to examine the impact of Good CorporateGovernanceâs Principleâs Implementation proxied by transparancy, independency,accountability, responsibility and fairness toward Financial Performance proxied byROA. The object of this study is PT. Angkasa Pura II (Persero). The study testedhypothesis using multiple regression analysis model.The results of this study showsthat transparancy, independency, accountability, responsibility and fairnesspositively influence financial performance significantly.Keywords: Transparancy, independency, accountability, responsibility, fairness,return on asset (ROA)